1986
DOI: 10.1007/bf00269709
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene formation by leucoplasts of Citrofortunella mitis and Citrus unshiu

Abstract: Leucoplasts of immature calamondin and satsuma fruits were incubated with [1-(14)C] isopentenyl pyrophosphate under various conditions. Optimal incorporation of the tracer into geranyl pyrophosphate and monoterpene hydrocarbons occurred in the presence of exogenous dimethylallyl pyrophosphate and Mn(2+) which was more effective than Mg(2+). The dependence of dimethylallyl pyrophosphate showed that about 10 moles were required for 1 mole of isopentenyl pyrophosphate for the best recovery in monoterpene hydrocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Immunocytochemical techniques using anti-GPP synthase antibodies should allow us to determine the exact subplastidial location, and also to test whether this enzyme is present in other types of plastids. As shown previously, leucoplasts from Citrofortunella mitis (Gleizes et al 1983;Gleizes et al 1987) or Citrus unshiu (Pauly et al 1986) and chromoplasts from Citrus sinensis (Perez et al 1990) or Narcissus pseudonarcissus L. (Mettal et al 1988) seem to possess a GPP synthase and the ability to synthesize hydrocarbon monoterpenes. As indicated by Perez etal.…”
Section: Determination Of the Intactness Of The Plastid Preparationmentioning
confidence: 65%
“…Immunocytochemical techniques using anti-GPP synthase antibodies should allow us to determine the exact subplastidial location, and also to test whether this enzyme is present in other types of plastids. As shown previously, leucoplasts from Citrofortunella mitis (Gleizes et al 1983;Gleizes et al 1987) or Citrus unshiu (Pauly et al 1986) and chromoplasts from Citrus sinensis (Perez et al 1990) or Narcissus pseudonarcissus L. (Mettal et al 1988) seem to possess a GPP synthase and the ability to synthesize hydrocarbon monoterpenes. As indicated by Perez etal.…”
Section: Determination Of the Intactness Of The Plastid Preparationmentioning
confidence: 65%
“…This evidence includes the correlation between the production of monoterpene secretion products and the presence of amoe-boid leucoplasts in the corresponding secretory cells (Cheniclet and Carde, 1985), the biosynthesis of unmodified monoterpenes by isolated leucoplasts (Pauly et al, 1986;Soler et al, 1992), and the documented origin of monoterpenes by the nonmevalonate pathway (Eisenreich et al, 1997;Sagner et al, 1998) that is known to be localized in plastids (Eisenreich et al, 1998;Lichtenthaler, 1999). In addition, both geranyl diphosphate synthase, which catalyzes the condensation of the primary metabolites isopentenyl diphosphate and dimethylallyl diphosphate to the acyclic precursor of monoterpenes, and (Ϫ)-limonene synthase, which catalyzes the first dedicated step of monoterpene biosynthesis in peppermint, are encoded as preproteins bearing N-terminal plastidial targeting sequences (Colby et al, 1993;Burke et al, 1999).…”
Section: Site Of Monoterpene Biosynthesis and Possible Secretory Mechmentioning
confidence: 99%
“…A geranyl pyrophosphate synthase has been isolated from the microorganism Micrococcus lysodeikticus where it functions in generating the primer for solanesyl pyrophosphate biosynthesis en route to menaquinone,62 and crude tissue extracts of monoterpene-producing plants do produce detectable levels of geranyl pyrophosphate from the relevant C5 precursors; however, farnesyl pyrophosphate is generally the major product in these systems. [63][64][65] Recently, soluble extracts from leaves of the common sage plant (Salvia officinalis; Lamiaceae) were fractionated by combination of gel permeation and hydrophobic interaction chromatography, largely to remove farnesyl pyrophosphate synthase, and shown to possess an electrophoretically distinct prenyltransferase that synthesizes, from dimethylallyl and isopentenyl pyrophosphate, geranyl pyrophosphate as the sole (>95%) product. 66 Moreover, selective extraction of the contents of the epidermal oil glands of sage leaves,67 the site of monoterpene biosynthesis and accumulation in this species,68 revealed that essentially all of the geranyl pyrophosphate synthase of the leaf tissue resided in these unique secretory structures.…”
Section: Introductionmentioning
confidence: 99%